"I Feel Guilty". Exploring Guilt-Related Dynamics in Family Caregivers of People with Dementia. Issue 5 (20th October 2022) - Gallego-Alberto, Laura; Losada, Andrés; Cabrera, Isabel; Romero-Moreno, Rosa; Pérez-Miguel, Ana; Pedroso-Chaparro, María Del Sequeros; Márquez-González, María
ABSTRACT: Objectives : Family caregivers of people with dementia often report feelings of guilt. However, the number of studies analyzing guilt and the factors associated with its appearance are scarce. The aim of this study is to explore the subjective experience of guilt in the family care of people with dementia. Methods : A qualitative analysis of the narratives of 13 family caregivers of people with dementia about their feelings of guilt was done. Results : Seven categories for understanding guilt in caregiving were obtained: guilt derived from actions themselves; guilt derived from one's limitations; guilt for feeling negative emotions; guilt associated with the change in the relationship with the person cared for; guilt for neglecting other areas; guilt induced by the person cared for, and guilt induced by others. The results showed the existence of cases in which guilt is absent by distress-avoiding processes. Conclusions : Guilt is a relevant variable in understanding caregiver distress, and its analysis is necessary for therapeutic work in the field of care. Clinical implications : Psychological interventions aimed at family caregivers should include specific techniques in order to address guilt feelings.